Cardiac regeneration: unraveling the complex network of intercellular crosstalk - Wu, Bailin; Constanty, Florian; Beisaw, Arica (Seminars in cell & developmental biology, 2025)
The heart is composed of multiple cell types, including cardiomyocytes, endothelial/endocardial cells, fibroblasts, resident immune cells and epicardium and crosstalk between these cell types is crucial for proper cardiac function and homeostasis. In response to cardiac injury or disease, cell-cell interactions and intercellular crosstalk contribute to remodeling to compensate reduced heart function. In some vertebrates, the heart can regenerate following cardiac injury. While cardiomyocytes play a crucial role in this process, additional cell types are necessary to create a pro-regenerative microenvironment in the injured heart. Here, we review recent literature regarding the importance of cellular crosstalk in promoting cardiac regeneration and provide insight into emerging technologies to investigate cell-cell interactions in vivo. Lastly, we explore recent studies highlighting the importance of inter-organ communication in response to injury and promotion of cardiac regeneration. Importantly, understanding how intercellular and inter-organ crosstalk promote cardiac regeneration is essential for the development of therapeutic strategies to stimulate regeneration in the human heart.